2022
DOI: 10.1080/13880209.2022.2099907
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicology, anti-lipase, and antioxidant effects of Callistemon citrinus in rats fed with a high fat-fructose diet

Abstract: Context Callistemon citrinus Skeels (Myrtaceae) exhibits many biological activities. Objective This study analyzes for the first time, the toxicity, obesogenic, and antioxidant effects of C. citrinus in rats fed with a high fat-fructose diet (HFFD). Materials and methods Four studies using male Wistar rats were conducted: (a) 7 groups ( n = 3): control (corn oil) and ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…Results of this investigation showed that HFF-diet for 12 weeks increased significantly pancreas and intestine lipase activity, body weight gain and altered serum lipid profile which is in agreement with previous reports [ 26 , [38] , [39] , [40] , [41] , [42] , [43] ]. These studies revealed that HFFD could induce obesity by several mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…Results of this investigation showed that HFF-diet for 12 weeks increased significantly pancreas and intestine lipase activity, body weight gain and altered serum lipid profile which is in agreement with previous reports [ 26 , [38] , [39] , [40] , [41] , [42] , [43] ]. These studies revealed that HFFD could induce obesity by several mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…of Callistemon citrinus and phospholipids were used. This dose has therapeutic efficacy against the inhibition of oxidative stress [ 15 , 32 ] and obesity amelioration [ 16 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A high-fat diet (HFD) containing 45.4% normal chow (Rodent diet brand Purina rat chow), 14.8% lard, 14.8% vegetable fat, and 25% fructose was daily prepared as reported in [ 16 ]. Fifty-four male Wistar rats were randomly divided into 9 ( n = 6) groups to be fed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Callistemon citrinus has been described as antimicrobial, anti-inflammatory, antiobesogenic, antioxidant and hepatoprotective [198,199]. The main bioactive components are terpenoids, phenolic acids and flavonoids (including eucalyptine, blumenol, gallic acid and protocatechuic acid) which have low oral bioavailability and absorption.…”
Section: Preclinical Studiesmentioning
confidence: 99%